2013
DOI: 10.1002/jobm.201300496
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles of Vibrio parahaemolyticus and its changes with environment

Abstract: The fatty acid (FA) profiles of 15 strains representing four genera (Vibrio, Pseudomonas, Aeromonas, and Shewanella) and seven species were compared by capillary gas chromatography with flame ionization detection. FA fingerprints of Vibrio parahaemolyticus were established by similarity calculation and principle component analysis. This provided a simple measure for distinguishing V. parahaemolyticus from other bacteria. The similarity scores indicated by correlation coefficient and vector cosine were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…618 and 414, respectively), which had a similar fatty acid profile under mesophilic conditions (Figure 4). As reported previously for other Vibrio isolates [52][53][54], the major fatty acids of these Vibrio strains were 16:1, 16:0, and 18:1. We found that the relative proportion of these fatty acids was temperature dependent for both Vibrio sp.…”
Section: Discussionsupporting
confidence: 85%
“…618 and 414, respectively), which had a similar fatty acid profile under mesophilic conditions (Figure 4). As reported previously for other Vibrio isolates [52][53][54], the major fatty acids of these Vibrio strains were 16:1, 16:0, and 18:1. We found that the relative proportion of these fatty acids was temperature dependent for both Vibrio sp.…”
Section: Discussionsupporting
confidence: 85%
“…In cyanobacteria, fatty acid biosynthesis is an essential and fundamental biochemical pathway which provides raw material for lipid synthesis. Fatty acids determine the organization and function of the cell membrane which is associated with the recognition of cell, specificity of species, and immunity of cell . Fatty acids are synthesized from the TCA cycle intermediate acetyl CoA and the esterification of fatty acids leads to the synthesis of lipids .…”
Section: Introductionmentioning
confidence: 99%